tRNA-like structures and gene regulation at the translational level: a case of molecular mimicry in Escherichia coli. - Springer, M (1989)
Escherichia coli threonyl-tRNA synthetase regulates the translation of its own mRNA by binding to it in a region, called the operator, located in front of the ribosomal binding site. The primary and secondary structures of the operator resemble those of the anticodon arm of several tRNA(Thr) isoacceptor species. We reasoned that if the interaction between the synthetase and its two partially analogous ligands, the tRNA and the mRNA, had some common features, single mutations in the enzyme should affect both interactions in a very similar way. We thus isolated synthetase mutants (called super-repressors) that repress the translation of their mRNA in trans to an extreme level, and other mutants that are completely unable to perform any repression. The super-repressors, which are suspected to bind their mRNA with high affinity, are shown to bind the tRNA with an increased affinity. The non-repressing mutants, which are suspected to have lost their capacity to bind the mRNA, are shown to bind their tRNA with less affinity. The binding properties of the mutant enzymes for the other substrates, ATP and threonine, are unchanged. The observed correlation between regulatory and aminoacylation defects strongly suggests that the synthetase recognizes the similar parts of its two RNA ligands--the anticodon-like arm of the mRNA and the true anticodon arm of the tRNA--in an analogous way.